2007
DOI: 10.1017/s0031182007002910
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cysteine peptidase activities inTrichobilharzia regentiandSchistosoma mansonicercariae

Abstract: Cercariae of the bird schistosome Trichobilharzia regenti and of the human schistosome Schistosoma mansoni employ proteases to invade the skin of their definitive hosts. To investigate whether a similar proteolytic mechanism is used by both species, cercarial extracts of T. regenti and S. mansoni were biochemically characterized, with the primary focus on cysteine peptidases. A similar pattern of cysteine peptidase activities was detected by zymography of cercarial extracts and their chromatographic fractions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…However, in another study, the reaction of antibodies raised against elastase of S. mansoni was observed neither with the penetration glands of T. szidati nor with the cercarial secretions on Western blots (180). In contrast, high activities of cysteine peptidases were noticed in induced cercarial secretions and homogenates for T. szidati and T. regenti (180,185). In addition, the presence of cercarial elastase in the latter species was not confirmed by screening of a cDNA library (186).…”
Section: Vertebrate Host Finding and Penetrationmentioning
confidence: 89%
“…However, in another study, the reaction of antibodies raised against elastase of S. mansoni was observed neither with the penetration glands of T. szidati nor with the cercarial secretions on Western blots (180). In contrast, high activities of cysteine peptidases were noticed in induced cercarial secretions and homogenates for T. szidati and T. regenti (180,185). In addition, the presence of cercarial elastase in the latter species was not confirmed by screening of a cDNA library (186).…”
Section: Vertebrate Host Finding and Penetrationmentioning
confidence: 89%
“…Interference of cathepsin L expression, however, had the greater impact on invasion possibly because the infective juvenile-specific cathepsin Ls are specifically adapted to this function. Cysteine proteases have also been implicated in the invasion process by the skin-penetrating parasites Schistosoma mansoni (37) and Trichobilharzia regenti (38) pointing to a common mechanism of host invasion among these trematodes.…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsin B and cathepsin L activities are readily detected by enzymatic assays in S. mansoni cercarial extracts and may facilitate skin penetration (Dalton et al, 1997; Kasný et al, 2007, 2009; Dvorák et al, 2008). 8–10 day old cultured larvae of S. mansoni also exhibited a dramatic increase in expression of these hemoglobin-degrading peptidases (Zerda et al, 1988; Dalton et al, 1995; Dalton and Brindley, 1996) and RNAi-mediated knockdown experiments showed that at least for SmCB1 the parasites cannot feed in vitro on hemoglobin and do not survive in vivo without this enzyme (Correnti et al, 2005).…”
mentioning
confidence: 99%